Faktor-Faktor Yang Mempengaruhi Environmental Disclosure Pada Perusahaan Industri di Singapore Exchange (SGX) - Nilam Putri; Indah Fajarini Sri Wahyuningrum (Jurnal Akuntansi Profesi, 2021)
This study aims to examine the effect of industry type, company size, leverage, auditor type, women directors, and managerial ownership on environmental disclosure. Environmental disclosure is measured using content analysis to determine the quantity of disclosure. The population of this study are industrial companies listed in the Singapore Exchange (SGX) during the period of 2017-2018. Purposive sampling is used as a sampling method, there are 61 companies as the research sample and 122 units of analysis to be used in this study. Multiple linear regression analysis was used to test the effect between variables. The data analysis technique used descriptive statistical analysis techniques and inferential statistical analysis techniques. The research showed that company size has a significant positive effect on environmental disclosure. Similar results are found in the leverage and the type of auditor who find a significant positive effect on environmental disclosure. Meanwhile, type of industry, women directors and managerial ownership do not have a significant effect on environmental disclosure. Based on the research results, large companies pay more attention to the public because of their credibility and reputation. Environmental disclosure is one way to maintain company credibility.